New records of host plants of Bactrocera carambolae Drew & Hancock, 1994 (Diptera: Tephritidae) in Cooperative Republic of Guyana - Costa, José Victor Torres Alves; Paes, Jefferson Luiz de Aguiar; Souza, Luiz Augusto Copati; Peters, Patricia; McWatt, Paul Michael; van Sauers-Muller, Alies; Sousa, Maria do Socorro Miranda de; Adaime, Ricardo (EntomoBrasilis, 2024)
Specimens of Bactrocera carambolae Drew & Hancock, 1994 (Diptera: Tephritidae) were obtained from fruits of Averrhoa bilimbi L., Averrhoa carambola L. (Oxalidaceae), Malpighia emarginata DC. (Malpighiaceae), and Psidium guajava L. (Myrtaceae), from a survey carried out in Lethem, Republic of Guyana. This is the first record of B. carambolae in A. bilimbi, M. emarginata and P. guajava in the country.